Pictet-Spengler cyclization in room temperature ionic liquid: a convenient access to tetrahydro beta-carbolines - Muthukrishnan, Murugan; More, Shivaji V.; Garud, Dinesh R.; Ramana, C. V.; Joshi, Rohini R.; Joshi, Ramesh A. (Journal of Heterocyclic Chemistry, 2006)
1,2,3,4-Tetrahydro-beta-carbolines have been synthesized in moderate to good yields in short reaction time using the ionic liquid [bbim] BF4 as reaction medium and promoter. There was no need for the use of an additional catalyst normally employed in Pictet-Spengler condensation.